Guide to Statutory Provisions in Public Sector Bargaining – Impasse Resolutions Procedures - Dion, Gérard (Relations industrielles / Industrial Relations, 1977)
This article reviews "Guide to Statutory Provisions in Public Sector Bargaining – Impasse Resolutions Procedures" by Helen S. Tanimoto.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z